Active learning in online teaching in SMA Swakarya Binjai (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
Nowadays, the education world in learning method is not only using a conventional method, which is basically, by an explanation from a teacher and merely from the learning books. But, with an effective and efficient learning method, so that the students are able to keep up and participate actively during the lesson, by taking an advantage of IT (Information Technology), especially for facing the changes in learning due to pandemic COVID-19. The contribution from people is one of the ways to carry out the socialisation of information technology. This community service, will be implemented in this research entitled "Active Learning in Online Teaching, in Swakarya Senior High School, Binjai", with an intention to assist teachers while in the process of learning, to be more interesting and enjoyable although it is done through a distance learning. The learning application will be given to all of the senior high school teachers, as is to prepare and use this learning application, in order to broaden the perception and to motivate the teachers, and eventually they will be able to motivate the students as well. Moreover, this will help to upgrade the quality of education.